(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The paper presents methods of using the methods of "matryeshka" and "consecutive grinding" to increase the level of students’ mastery of complex topics of theoretical mechanics. It also explains how to use these methods to calculate the derivatives of complex functions and to express the angular momentum of a point in various coordinate systems.